Masters of Mischief - Russell, Rachel Renee (New York Aladdin, 2019)
Max and Erin continue the fight to protect South Ridge Middle School from Ralph and his henchmen, but Max's greatest challenge may be keeping his crush on Erin a secret.
640L
Ages 9-13.
107517
Keywords: Heroes -- Juvenile fiction; Middle schools; Schools; Robbers and outlaws; Humorous stories; Juvenile Fiction -- Comics & Graphic Novels -- General; Juvenile Fiction -- Social Issues -- Friendship; Heroes and heroines; School stories; Humorous fiction; Juvenile works